Direct Energy Extraction from Brown Macroalgae‐Derived Alginate by Gold Nanoparticles on Functionalized Carbon Nanotubes. Issue 1 (18th September 2013) - Hoa, Le Quynh; Yoshikawa, Hiroyuki; Saito, Masato; Ueda, Mitsuyoshi; Shibata, Toshiyuki; Tamiya, Eiichi
Abstract The viability of employing brown macroalgae as a future renewable energy and chemical resource has so far proven to be challenging because of the low efficiency of the energy extraction process from alginate, which forms the principle, difficult‐to‐degrade component. In contrast to currently employed alginate‐metabolizing microbial approaches, we here extract energy from macroalgae, for the first time, through a fuel cell system that exploits the electrochemical oxidation of alginate by gold nanoparticle‐decorated functionalized carbon nanotubes without any external input of energy. The analyses suggest that the electrochemical oxidation process induces partial oxidation of alginate and, in addition to bioenergy, also yields valuable chemicals, which paves the way for the future production of energy and feedstock materials from inedible biomass.